Does 'Animal Fun' improve aiming and catching, and balance skills in young children?. (January 2019) - De Oliveira, Jorge A.; Rigoli, Daniela; Kane, Robert; McLaren, Sue; Goulardins, Juliana B.; Straker, Leon M.; Dender, Alma; Rooney, Rosanna; Piek, Jan P.
Highlights: Results demonstrate the efficacy of Animal Fun in improving one-leg balance for young children. Animal Fun improved throwing skills for children with poorer motor proficiency. Animal Fun improved the social and behavioural functioning in young children. Abstract: Aim: The Animal Fun program, a universal early intervention program that aims to promote the motor skills and social-emotional development of young children, has shown to improve overall motor proficiency and social and behavioural outcomes. The aim of the current study was to evaluate the program's impact on children's aiming and catching, and balance skills. Methods: A cluster randomised control trial was employed, with six intervention and six control (following normal curriculum) schools. A total sample of 511 children (257 boys and 254 girls), aged 4–6 years presented at pre-test. Children were tested across three time points, pre-test, post intervention (six months later) and follow-up (18 months after pre-test), using the Movement Assessment Battery for Children-2 Aiming and Catching, and Balance tasks. The study also tested for potential moderators including pre-test motor proficiency, age, gender, and cognitive performance. Results: Participation in Animal Fun improved children's one leg balance at post-test and follow-up compared to control children, regardless of pre-test motor proficiency, age, gender, or pre-test cognitive performance. Participation in Animal Fun also improved throwing skills for those children with poorer motor proficiency compared to the controls with poorer motor performance. Interestingly, it was found that the control group's catching skills improved more than the intervention group at follow up. Conclusions: The study provides some promising results regarding the efficacy of the Animal Fun program in improving one-leg balance for all children, and throwing skills for those children with poorer motor proficiency, while also suggesting potential confounding factors, such as maturational issues and other individual factors (e.g., a child's participation in extracurricular activity).